Empowering MSMEs Through Digital Enablement: The Direct Effects of Internet Training, Capacity Development, and Motivation on Business Performance - Lisnatiawati Saragih; Iwan Firdaus (Universitas Mercu Buana, 2026)
The acceleration of digital transformation among Micro, Small, and Medium Enterprises (MSMEs) is essential for improving competitiveness and economic resilience in the digital era. This study examines the effects of Internet Learning, Digital Capacity Development, and Internet Motivation on MSME Digital Readiness in the Indonesian context. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), the findings indicate that all three predictors significantly and positively influence digital readiness, with Internet Motivation emerging as the most dominant factor. These results highlight the importance of combining technical knowledge, supportive infrastructure, and psychological engagement to foster a digitally ready MSME sector. The study offers a multidimensional framework of digital readiness by integrating cognitive, structural, and behavioural elements. It also provides practical implications for policymakers and development institutions to implement integrated digital literacy, capacity building, and motivation-driven strategies. Future studies are encouraged to explore contextual variations and adopt longitudinal or mixed-method designs to deepen understanding of digital transformation in diverse MSME environments.